Colour Fading of Textile Fabric by Plasma Treatment. (8th January 2013) - Cheung, H. F.; Kan, C. W.; Yuen, C. W. M.; Yip, J.; Law, M. C.
Abstract : Colour fading of a reactive dye (C.I. Reactive Blue 19) dyed textile fabric was performed by atmospheric pressure plasma (APP) treatment with the use of plasma jet. Under the APP treatment condition of treatment time = 5 sec/mm; ignition power = 160 W; oxygen concentration = 1%; jet distance = 3 mm, significant colour-fading effect was achieved. For comparison purpose, the reactive dye dyed textile fabric was subjected to conventional enzymatic colour-fading process. Experimental results revealed that the APP-induced colour-fading effect was comparable with conventional enzymatic colour-fading process.